Essays in toxicology. - Hayes, Wayland J., Jr. (Wayland Jackson), 1917-1993
Essays in Toxicology, Volume 6 approaches toxicology by very different routes; two essays with materials (plastics and tobacco alkaloids), one deals with the effects of abnormal pressure, one considers the biochemistry of the lung, and one discusses poison control centers and other mechanisms for limiting the injury done by toxic materials. The book presents essays on the topological problems and untoward effects from plastic devices used in medical applications; the metabolism of tobacco alkaloids; and poisons control center. The text also includes essays on the toxicology of hypobaric and hy.